WILHELM GRÜTTER: A name among seafaring men - Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
(A history of the training ship 'General Botha'). Cape Town, 1973, pp 173. Until recently, the South African Navy could claim the dubious distinction that of all three arms of the Defence Force, its history was the least adequately chronicled. At last the unfavourable balance has been redressed through the publication of two excellent books, that under review being the second to appeal'.